Selective recovery of valuable metals from industrial waste lithium-ion batteries using citric acid under reductive conditions: Leaching optimization and kinetic analysis - Meng, Fei; Liu, Qingcai; Kim, Rina; Wang, Jingxiu; Liu, Gui; Ghahreman, Ahmad (Hydrometallurgy, 2020)
Recycling of valuable metals from waste lithium-ion batteries (LIBs) has recently attracted significant attention due to the environmental and economical concerns. In this paper, a simple and economical leaching process based on citric acid system was developed for the leaching of metals from the industrial waste LIBs without the manual separation of current collectors, i.e. copper and aluminum foils. The results showed significantly higher leaching efficiencies of metals due to the presence of copper and aluminum. About 91% Li, 90% Co, 94% Ni and 89% Mn were leached under the optimum leaching conditions of 0.5 mol/L citric acid, solid to liquid (S/L) ratio of 80 g/L at 90 °C for 80 min. Furthermore, the effects of the addition time and species of reductant on the leaching of Li, Co, Ni, and Mn were investigated, and the selectivity over Cu and Al as well. The kinetics data revealed that the leaching of Li, Co, Ni and Mn fitted best to the Avrami equation controlled by the surface chemical reaction, whilst the leaching of Cu and Al corresponded to the surface chemical-controlled reaction based on shrinking core model. The leaching feed before and after leaching were characterized by X-ray diffraction (XRD) and scanning electron microscopy (SEM). [Display omitted] •A simple leaching process based on citric acid system for recycling of LIBs.•About 90% of Li, Co, Ni and Mn were leached with current collectors in the absence of reductant.•The leaching of Li, Co, Ni and Mn followed the Avrami equation.•The reductant of ascorbic acid exhibits better selectivity than H2O2.•Delayed addition of reductant results in better metals leaching.